Financial Liquidity Strategies of Mining Enterprises in Poland and in the World - Aneta MICHALAK (Communications of International Proceedings, 2020)
Financial liquidity strategies are one of the most important decision-making problems in an enterprise. The article attempts to discuss and examine the liquidity strategies used in the hard coal mining industry in Poland and in the world. The paper puts forward a thesis that due to the high degree of immobilization of assets, mining enterprises use conservative liquidity strategies. The nature of the liquidity strategy was defined on the basis of the financial liquidity ratios: current ratio, quick ratio and cash ratio. The analysis was complemented with the establishment of the working capital. This allowed to characterise the liquidity strategies used in the hard coal mining industry. The research was based on literature studies and data from the financial statements of the surveyed enterprises. The conducted analysis is of preliminary study nature and will be extended in further works by extending the methodology of liquidity measurement.
Keywords: Financial Liquidity; Working Capital; Mining Enterprises.